Water-Saving Tips With a Visualized Indicator Related to the Environment - Otaki, Yurina; Maeda, Asahi (Frontiers in Water, 2022)
Water-saving tips are information-based interventions aimed at managing water demand. Studies of the effectiveness of qualitative water-saving tips to explain why and how water should be saved have not always found significant changes in water consumption. Some studies indicate that the addition of quantitative tips and videos are effective for water conservation. This study adds to the literature by attempting to verify the effectiveness of water-saving tips that visualize the amount of water that can be saved using illustrations of bathtubs. Furthermore, as not all people are interested in water saving, we include tips with a visualized indicator related to the environment, which is of more general interest. These tips used CO2 emissions reductions to demonstrate the effect of water saving. As a result, for high-consumption households, it is more effective to present water-saving tips that present information on how their actions can limit CO2 emissions than to illustrate the reduction in water consumption directly. At the same time, for low-consumption households, none of the tips had water-saving or boomerang effects (i.e., increased the consumption while planning to reduce). Households were divided into high- and low-consumption using baseline water consumption per capita for their household size. The results of this study could serve as a tool for water demand management that can be easily utilized in many parts of the world.